Evaluasi Nilai Heterosis dan Heterobeltiosis Pada Persilangan Dialel Tanaman Jagung Madura (Zea mays L.) - Achmad Amzeri (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2016)
ABSTRACT The identification of heterosis and heterobeltiosis in a dialel cross between the Madura inbred lines is needed as a basis for assembling hybrid maize varieties that suitable for development in Madura. This study aimed to identify the combination of crosses that showed the best heterosis and heterobeltiosis values ​​for early maturity, production support and production per hectare characters. This research was conducted at The Experimental Station of Agricultural Faculty of Madura Trunojoyo University. Plant material used were 6 inbred lines of madura maize (UTM 2, UTM 7, UTM 14, UTM 14, UTM 15, UTM 18, and UTM 22), and 30 full-dielel cross hybrids between 6 genotypes of inbred lines. The experiments used the randomized complete block design (RCBD) three replications so that there were 108 experimental units. The observed characters were flowering age, harvest age, cob diameter, cob length, weght of 100 seed, and production per hectare. The crosses that produced the best heterosis and heterosbeltiosis values ​​for early maturity were UTM14 x UTM18, UTM15 x UTM2 and UTM18 x UTM2. The crosses for the character of cob diameter, cob length and the weight of 100 seeds mostly result in heterosis and heterobeltiosis values ​​are positive. On the character of production per hectare the highest heterosis and heterobeltiosis values ​​were crossed UTM2 x UTM14 (214,742%) and UTM2 x UTM18 (171,585%).